Uso de CSP na Especificação Formal do Nível Micro-Organizacional de SMAs - Barbosa, Raquel M.; Costa, Antônio C. R.; Tedesco, Patrícia C. A. R.; Mota, Alexandre C. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2010)
This paper explores the use of the CSP language for the formal specification of multiagent systems organizations. It shows that CSP can be used to specify parts of the micro-organizational level of multiagent systems, namely, behaviors of organizational roles and exchange processes between organizational roles. An example of the use of CSP and of the FDR model checker for such purpose is presented.